Effect of Dumbell Thera Band Exercise and Bow Training on the Archery Accuracy - Burhannandra Dwi Astanto; Sri Winarni; Betrix Teofa Perkasa Wibafied Billy Yachsie; Amri Hartanto; Afeb Chesa Arianto (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of dumbell thera band and bow training on accuracy of archery athletes. This research is an experiment with a two groups pretest posttest design. The sample consisted of 24 athletes who were given treatment for 16 meetings. The instrument used the archery scoring test at a distance of 40m. The test for normality was done using skolmogorov smirnov and the homogeneity test with levene test at the significance level of 5% (p> 0.05). Hypothesis testing was performed using paired samples t-test. The results indicated that (a) there is an effect of dumbell thera band exercise on the accuracy of archery athletes, (b) there is an effect of bow training on the accuracy of archery athletes, and (c) there is a difference in the influence between the exercises dumbell thera band and bow training in increasing the accuracy of archery athletes, where dumbell thera band exercise has a greater effect in improving archery accuracy.